Prognostic Value of Residual Tumor Size in Patients With Epithelial Ovarian Cancer FIGO Stages IIA–IV: Analysis of the OVCAD Data. Issue 3 (1st March 2012) - Polterauer, Stephan; Vergote, Ignace; Concin, Nicole; Braicu, Ioana; Chekerov, Radoslav; Mahner, Sven; Woelber, Linn; Cadron, Isabelle; Van Gorp, Toon; Zeillinger, Robert; Castillo-Tong, Dan Cacsire; Sehouli, Jalid
Abstract : Objective: The objective of the study was to evaluate the prognostic impact of residual tumor size after cytoreductive surgery in patients with epithelial ovarian cancer. Methods: In this prospective, multicenter study, 226 patients with epithelial ovarian cancer (International Federation of Gynecology and Obstetrics stages IIA–IV) were included. Patients were treated with cytoreductive surgery and adjuvant platinum-based chemotherapy. Univariate and multivariable survival analyses were performed to investigate the impact of residual tumor size on progression-free and overall survival. Results: In 69.4% of patients, surgery resulted in complete tumor resection; minimal residual disease (≤1 cm) was achieved in 87.2% of patients. Advanced tumor stage was associated with a lower rate of complete tumor resection ( P < 0.001). After cytoreductive surgery, 3-year overall survival rates were 72.4%, 65.8%, and 45.2% for patients without, with minimal, and with gross residual disease (>1 cm), respectively ( P < 0.001). Multivariable survival analysis revealed residual tumor size ( P = 0.04) and older patient age ( P = 0.02) as independent prognosticators for impaired overall survival. Complete cytoreduction was predictive for a higher rate of treatment response ( P = 0.001) and was associated with prolonged progression-free and overall survival ( P < 0.001 and P = 0.001). Conclusions: The size of residual disease after cytoreduction is one of the most crucial prognostic factors for patients with ovarian cancer. Patients after complete cytoreduction have a superior outcome compared with patients with residual disease. Leaving no residual tumor has to be the aim of primary surgery for ovarian cancer; therefore, patients should receive treatment at centers able to undertake complex cytoreductive procedures.